PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA PEGAWAI BIRO UMUM DAN LAYANAN PENGADAAN, KEMENTERIAN DESA, PEMBANGUNAN DAERAH TERTINGGAL DAN TRANSMIGRASI - Kiki Nur Wijayanti; Donny Dharmawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to determine the effect of work environment and compensation on job satisfaction. The population in this study were employees at the Bureau of General Affairs and Procurement Services. The technique used for sampling using simple random sampling method with a quantitative approach. The data used in this research is primary data obtained by distributing questionnaires to employees at the Bureau of General Affairs and Procurement Services as respondents. The results showed that simultaneously the work environment and compensation variables had a positive and significant effect on job satisfaction. While the partial results show that the work environment variable has No. significant effect on job satisfaction. While the compensation variable has a positive and significant effect on job satisfaction.